Challenges in mentoring at-risk young adults: caseworkers' perspective. Issue 3 (3rd July 2019) - Sulimani-Aidan, Yafit
ABSTRACT: This exploratory study examines the barriers, challenges and needs of 30 caseworkers who mentor at-risk young adults during the transition to adulthood. Professional mentoring relationships are an important source of support for at-risk young people. However, literature concerning the mentoring relationship from the perspective of the mentors is scarce. The theoretical thematic analysis revealed two major themes. The first theme- included challenges related to the young adults' personal histories and characteristics. The second major theme related to the mentors' expertise within their own services. The most dominant needs during the mentoring process were broad and current knowledge and ongoing training and support. The findings are discussed in relation to the mentoring literature and emerging adulthood theory. Implications for practice highlight the importance of the design and assimilation of programs that enable the promotion of meaningful mentoring relationships via organisational modifications.